Dynamic behavior of resistive random access memories (RRAMS) based on plastic semiconductor (RRAMS) based on plastic semiconductor - Rocha, Paulo R. F. (2012)
Resistive Random Access Memories based on metal-oxide polymer diodes are characterized. The dynamic behavior is studied by recording current-voltage characteristics with varying voltage ramp speed. It is demonstrated that these organic memory devices have an internal capacitive double-layer structure, which inhibits the switching at high ramp rates (1000 V/s). This behavior is modeled and explained in terms of an equivalent circuit.